Migration in Poland in the Context of the EU Comprehensive Migration Policy - Wysokińska, Agnieszka (Comparative Economic Research. Central and Eastern Europe, 2008)
The aim of the paper is to present main tendencies in the migration processes in Poland as the new member country of the European Union after the accession. Poland as the largest New Member State of the EU started to be first of all the country of highest emigration in the region, especially to the United Kingdom and Ireland. The immigration into Poland increased also after the accession to the EU, according to the new rules of the Common Comprehensive Migration Policy. This situation is deeply connected with the expectations of the labour market in Poland and in other EU member countries.